Cracks Reinforce the Interactions among Soil Bacterial Communities in the Coal Mining Area of Loess Plateau, China - Luo, Zhanbin (Int J Environ Res Public Health, 2019)
Soil microorganisms play a key role in global biogeochemical changes. To understand the interactions among soil bacterial communities and their responses to extreme environments, the soil properties and bacterial community diversity were determined in the post-mining ecosystem of the Loess Plateau, China. The results showed that the soil temperature, pH, organic matter, available phosphorus, and available potassium values were significantly reduced in the post-mining cracks area. However, the richness and uniformity of soil bacterial communities increased by about 50% in the post-mining cracks area. Soil microbial community structure and the network interactions tended to be complex and strengthened in the post-mining cracks area. Moreover, soil nutrient loss caused the differences in soil bacterial community structure compositions in the post-mining cracks area. Furthermore, the relationships between soil physicochemical properties and different modules of the soil bacterial molecular ecological network were changed in a complex manner in the post-mining cracks area. This study provides a theoretical basis for adaptive management and response to cracks in post-mining areas and under other extreme conditions.